2002
DOI: 10.1002/1521-4141(200206)32:6<1764::aid-immu1764>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

T helper differentiation in resistant and susceptible B7-deficient mice infected with Leishmania major

Abstract: The contribution of the costimulatory molecules B7–1 and B7–2 to the in vivo differentiation of Th cells remains controversial. The infection of resistant and susceptible strains of mice with the parasite Leishmania major provides a well‐established model for studying in vivo differentiation of CD4+ T cells. We have infected B7–1/B7‐2‐deficient mice onthe BALB/c and 129 background with L. major and subsequently examined different parameters of infection and cytokine responses upon restimulation of lymph node c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The administration of CTLA4-Ig decreases the parasite load at the site of injection from 10 4 to 10 2 parasites (17). This reduction of parasite burden correlates with a switch from predominant IL-4 to predominant IFN-g secretion by CD4 + T cells; similar findings were made with CD86-deficient BALB/c mice (18). In another experimental system, CD4 T cells from transgenic mice that secrete soluble CTLA4-Ig into the circulation produced more IFN-g and less IL-4 than wild-type mice in response to immunization with DNPkeyhole limpet hemocyanin in alum (19).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The administration of CTLA4-Ig decreases the parasite load at the site of injection from 10 4 to 10 2 parasites (17). This reduction of parasite burden correlates with a switch from predominant IL-4 to predominant IFN-g secretion by CD4 + T cells; similar findings were made with CD86-deficient BALB/c mice (18). In another experimental system, CD4 T cells from transgenic mice that secrete soluble CTLA4-Ig into the circulation produced more IFN-g and less IL-4 than wild-type mice in response to immunization with DNPkeyhole limpet hemocyanin in alum (19).…”
Section: Discussionsupporting
confidence: 71%
“…Studies have identified basophils (7,8) and NKT cells (9) as the critical source of IL-4, whereas other studies demonstrate that naive CD4 T cells themselves produce sufficient levels of IL-4 for the development of Th2 cells (10)(11)(12). Yet other studies have implicated various costimulatory molecule receptors, such as OX-40 (13,14), ICOS (15), and CD28 (16)(17)(18)(19), in the differential development of Th2 over Th1 cells. Although costimulation is typically considered to be delivered to a T cell by an APC, functional interactions between T cells via costimulatory molecules and their receptors have been described (20); this is especially true for CD28 and the CD80/86 costimulatory molecules (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Furthermore, antibody blockade of B7-2, but not B7-1 led to an increased T cell response resulting in diminished parasite load (Murphy, Cotterell, Gorak, Engwerda, & Kaye, 1998; Murphy, Engwerda, Gorak, & Kaye, 1997). This is further supported by studies with L. major infected B7-1 knockout, B7-2 knockout, and B7-1/B7-2 double knockout BALB/c mice (Brown et al, 2002). Signaling via CD40-CD40L interactions, critical for the induction of anti-leishmanial responses (Campbell et al, 1996; Kamanaka et al, 1996), is also impaired by L. major (Awasthi et al, 2003).…”
Section: Mechanisms Of Immune Evasionmentioning
confidence: 76%
“…Using CTLA4Ig to block B7/CD28 interaction during Leishmania major infection in BALB/c mice, Corry and colleagues (26) showed that priming of Th2 cells was more dependent on B7/ CD28 pathway than the priming of Th1 cells. Subsequently, it was shown that B7.2 is important for Th2 induction in the susceptible BALB/c mice, and absence of B7.2 alone or the combined absence of B7.1 and B7.2 induced resistance to leishmaniasis in these mice (27,28). However, BALB/c mice deficient in B7.1 remain as susceptible as wild-type (WT) 4 BALB/c mice (27).…”
mentioning
confidence: 99%
“…Subsequently, it was shown that B7.2 is important for Th2 induction in the susceptible BALB/c mice, and absence of B7.2 alone or the combined absence of B7.1 and B7.2 induced resistance to leishmaniasis in these mice (27,28). However, BALB/c mice deficient in B7.1 remain as susceptible as wild-type (WT) 4 BALB/c mice (27). Interestingly though, absence of B7.2 had no influence on disease phenotype in the resistant 129 mouse strain (27).…”
mentioning
confidence: 99%